Natural Product Alantolactone Targeting AKR1C1 Suppresses Cell Proliferation and Metastasis in Non-Small-Cell Lung Cancer - Fu, Zhiwen; Li, Shijun; Liu, Jinmei; Zhang, Cong; Jian, Chen; Wang, Lulu; Zhang, Yu; Shi, Chen (Frontiers in Pharmacology, 2022)
Non-small cell lung cancer (NSCLC) is one of the leading causes of cancer-related deaths, characterized by highly invasion and metastasis. Aldo-keto reductase family 1 member C1 (AKR1C1) plays an important role in cancer cell proliferation and metastasis and has gained attention as an anticancer drug target. Here we report that the natural sesquiterpene lactone alantolactone (ALA) was shown to bind directly to AKR1C1 through the Proteome Integral Solubility Alteration (PISA) analysis, a label-free target identification approach based on thermal proteome profiling. Acting as a specific inhibitor of AKR1C1, ALA selectively inhibit the activity of AKR1C1 and ALA treatment in human non-small cell lung cancer (NSCLC) cells results in a reduction in cell proliferation and metastasis, inhibition of AKR1C1 expression, and deactivation of STAT3. Moreover, ALA inhibited tumor growth in vivo and the inhibition of AKR1C1 and STAT3 activation were also found in the murine xenograft model. Collectively, our work not only give mechanistic insights to explain the bioactivity of ALA in anticancer but also provide opportunities of developing novel sesquiterpene lactone-based AKR1C1 inhibitors for treatment of NSCLC.